NILAI-NILAI MULTIKULTURAL DAN PENDIDIKAN ISLAM DALAM TRADISI TEREMPOH MELAYU SINTANG - Dian Findhiani Eka Hadi Lestari; Syamsul Kurniawan (Journal of Research and Thought on Islamic Education, 2018)
This research is a study of the trempoh tradition that was carried out by the Malay community in sub-district Sintang, Districts Sintang, province West Borneo. The trempoh tradition is a repertoire of local culture that serves as a means of friendship and unifying between tribes, religions and ethnicities living in sub-district Sintang. This research determine to know how the implementation, multicultural values, and Islamic education values from the trempoh tradition. This research is a field research that uses descriptive qualitative method to describe the implementation and values of the tradition that are supplanted through observation, interviews and documents related to the tradition. The results of this study explain that the implementation of the trempoh tradition consists of the takbiran activities, family terempoh, male trempoh, female trempoh, and family terempoh. In the trempoh traditions there are multicultural values, such as: diversity, equality, humanity, justice, and democracy, while the Islamic education values from trempoh traditions, such as: religious, compassion, politeness, and social care. Penelitian ini merupakan studi terhadap tradisi terempoh yang dilakukan oleh masyarakat Melayu di Kecamatan Sintang, Kabupaten Sintang, Provinsi Kalimantan Barat. Tradisi terempoh merupakan khasanah budaya lokal yang berfungsi sebagai sarana silaturahmi dan pemersatu antar suku, agama dan etnis yang tinggal di Kecamatan Sintang. Penelitian ini bertujuan untuk mengetahui pelaksanaan, nilai-nilai multikultur, dan nilai-nilai pendidikan Islam dari tradisi terempoh. Penelitian ini merupakan penelitian lapangan yang menggunakan metode deskriptif kualitatif untuk memaparkan pelaksanaan dan nilai-nilai dari tradisi terempoh melalui observasi, wawancara dan dokumen terkait tradisi terempoh. Hasil penelitian ini menjelaskan bahwa pelaksanaan tradisi terempoh terdiri dari kegiatan takbiran keliling, terempoh keluarga, terempoh laki-laki, terempoh perempuan, dan terempoh kaum kerabat. Dalam tradisi terempoh terdapat nilai-nilai multikultural, berupa: keragaman, kesetaraan, kemanusiaan, keadilan, dan demokrasi, sementara nilai-nilai pendidikan Islam dari tradisi terempoh, yaitu: religius, kasih sayang, kesantunan, dan kepedulian sosial.